Ewolucja opodatkowania przedsiębiorstw zagranicznych prowadzących działalność gospodarczą w Polsce - Małecki, Jerzy (Wydział Prawa i Administracji UAM, 1991)
Nationalization and political and economic changes implemented after the II World War have never eliminated the economic activity of foreign investors in Poland. Taxation of foreign legal and natural persons conducting their economic activity in Poland is based on two sets of legal regulations: - international agreements on the prevention of double taxation and on the promotion and protection of foreign investment, - domestic tax legislation regulating the taxation of domestic units and special provisions applicable exclusively to foreign investors. Hitherto existing evolution of taxation consisted in concluding newer and newer international agreements protecting financial interests of foreign investors. The reconstruction of the Polish tax system is carried out with the principle of generality and equality of taxation in mind. It means that special regulations addressed to some selected group of taxpayers, including foreign investors, will gradually disappear. The efficiency of a given economic unit must be verified by market, and not by tax privileges granted by the state.
Evolution of taxation of foreign companies conducting their economic activity in Poland